Self-Directed Learning Model Based on Local Wisdom Values on Student Learning Outcomes - Hilya Puspita; Fery Muhamad Firdaus; Sekar Purbarini Kawuryan (Journal of Innovation in Educational and Cultural Research, 2024)
Learning models are increasingly varied according to the developments and needs of the times. The delivery of learning materials in elementary schools is usually based on books provided by the government, even though learning materials should be taken from local wisdom in the students' environment. This study aims to determine the effect of the self-directed learning model based on local wisdom values on student learning outcomes. This study used a quasi-experimental research type with a one-group pre–test–post–test research design with a total of 27 students, including 15 boys and 12 girls. The data collection method used a questionnaire. The data analysis used was: 1) Descriptive statistics; 2) Analysis assumption test; and 3) Hypothesis testing. The results show that the self-directed learning model based on local wisdom has a significant effect on student learning outcomes, as evidenced by 27 students, 19 students experienced an increase, and no students experienced a decrease in learning outcomes. This research has implications for the education sector to increase knowledge about self-directed learning models that can improve student learning outcomes to become individuals better prepared to face the challenges of the times.